Microwave-enhanced, stereospecific ring-closure of medium-ring cyanamide ethers to yohimbine. Issue 17 (25th April 2019) - Paciaroni, Nicholas G.; Norwood, Verrill M.; Garcia, Daniel E.; Huigens, Robert W.
Graphical abstract: Highlights: Cyanamides react as nucleophiles with resonance-stabilized carbocation centers. This SN 1 reaction shows complete stereospecificity to form a single diastereomer. Cyanamide ring-closure to yohimbine requires 1 min under microwave irradiation. Abstract: A highly efficient acid-promoted, stereospecific, transannular ring-closure of medium-ring ether compounds to the indole alkaloid yohimbine is described. Microwave-enhanced acetic acid degradation of cyanamide compounds involves loss of (R)- or (S)- ethers, followed by a stereospecific, nucleophilic ring-closure from the cyanamide to afford yohimbine in up to 74% yield in as little as one minute. This nucleophilic reactivity of the amino moiety of the cyanamide highlights an alternative reactivity profile from its traditional electrophilic properties. Additionally, this reaction pathway highlights a rare case of an SN 1 pathway that proceeds with complete stereospecificity.